Pengaruh Model Pembelajaran Berbasis Masalah terhadap Kemampuan Membaca Permulaan Anak Usia 5-6 Tahun - Resky Riswana Ardi Putri; Parwoto; Rusmayadi (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2023)
The research aims to ascertain the impact of the problem-based learning model on the early reading skills of children in Ar-Rahim Kindergarten aged 5-6 years. The approach used in this research is quantitative with the Quasi-Experimental Design type. With a population of 38 students using simple random sampling. With a sample of 6 students in the experimental and control groups. This proves that students who received treatment using the problem-based learning model improved their initial reading skills better than students who received treatment in the control group. This research uses descriptive statistical analysis and non-parametric statistical analysis. In the research, the results of Tcount were 83 and Ttable 2.228, so we got Tcount 83 > Ttable 2.228 and Zcount 2.15 > Ztabel 0.4842 = H0 was rejected, and H1 was accepted, indicating that there is an influence of the problem-based learning model on children's early reading skills, in terms of This shows that the problem-based learning model has an impact on children's reading abilities and is better than children who received treatment in the control group.